Kewenangan Pemerintah Daerah dalam Penegakan Protokol Kesehatan pada Pilkada Kabupaten Serang - Rio Gobirthdi; H E Rakhmat Jazuli (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
After the implementation of Covid-19 as a global pandemic that affects aspects of public health, it turns out to have an effect and spread to other aspects. In Indonesia itself, it has an impact on aspects of the government, namely the center and the regions for handling Covid-19. The holding of simultaneous regional elections during the Covid-19 pandemic has attracted the attention of local governments, one of which is the Serang Regency government because it is feared that the implementation of these elections could violate health protocols. The author is also interested in examining how the authority of the local government in enforcing health protocols in the regional elections of Serang Regency is based on Banten Governor Regulation Number 38 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an Effort to Prevent and Control Covid-19? and how are the sanctions given to violators of health protocols in the elections in Serang Regency during the Covid-19 pandemic?This study uses empirical juridical research methods by analyzing data based on data sources, namely primary data materials with interviews with the Covid-19 Task Force, KPU and Bawaslu of Serang Regency and then analyzed qualitatively based on the research described in the form of data analysis obtained at the time of the study.The results of the research on the authority of the local government in enforcing health protocols in the regional elections of Serang Regency based on Banten Governor Regulation Number 38 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as Covid-19 Prevention and Control Efforts refer to KPU Regulation Number 6 of 2020 concerning the Implementation of the Governor Election and Deputy Governors, Regents and Deputy Regents, and/or Mayors and Deputy Mayors simultaneously continue in the Covid-19 Non-Natural Disaster conditions, namely through the Covid-19 Task Force, KPU and Serang Regency Bawaslu. Meanwhile, sanctions given to violators of health protocols in the elections in Serang Regency during the Covid-19 pandemic are sanctions in the form of verbal or written warnings, social work, and administrative fines, in Article 10 of Governor Regulation Number 38 of 2020 and Articles 5, 6, 7, and 8 KPU Regulation Number 6 of 2020.